A Medal for Benny Movie Still - Paramount Pictures:::Creator::::::::::::
Lolita Sierra (Dorothy Lamour), Joe Morales (Arturo de Cordova) and Chito Sierra (Fernando Alvarado) in Paramount Pictures 1945 production of 'A Medal for Benny.' Morales is showing Sierra the new boat he has bought (with borrowed money). The boat promptly sinks when Morales takes Sierra on a trip in the boat. According to caption, the production company was giving Lamour and de Cordova an opportunity to show their talents with this movie.